2010
DOI: 10.1007/s10588-010-9076-0
|View full text |Cite
|
Sign up to set email alerts
|

Measuring CMOT’s intellectual structure and its development

Abstract: Computational Organization Theory is often described as a multidisciplinary and fast-moving field which can make it difficult to keep track of it. The recent inclusion of Computational and Mathematical Organization Theory (CMOT) into the Social Science Citation Index offers a good reason to take stock of what has happened since the foundation of the journal and to analyze its intellectual structure and development from 1995 to 2008. We identify the most influential publications by means of citation analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…We considered the four years from 2010 to 2013. Since our interest lies in the management and organizational behavior literature, we screened the two simulation journals that have the closest ties with our Zou and Yilmaz (2011) discipline (Meyer et al 2009(Meyer et al , 2011: Computational and Mathematical Organization Theory and the Journal of Artificial Societies and Social Simulation. Then, we also screened articles published in a list of top management journals (based on ISI Thompson's Impact Factor) and decided to include the four presenting ABM-related publications (Table 1): Organization Science, Journal of Management Studies, Strategic Management Journal, and MIS Quarterly.…”
Section: Methodsmentioning
confidence: 99%
“…We considered the four years from 2010 to 2013. Since our interest lies in the management and organizational behavior literature, we screened the two simulation journals that have the closest ties with our Zou and Yilmaz (2011) discipline (Meyer et al 2009(Meyer et al , 2011: Computational and Mathematical Organization Theory and the Journal of Artificial Societies and Social Simulation. Then, we also screened articles published in a list of top management journals (based on ISI Thompson's Impact Factor) and decided to include the four presenting ABM-related publications (Table 1): Organization Science, Journal of Management Studies, Strategic Management Journal, and MIS Quarterly.…”
Section: Methodsmentioning
confidence: 99%
“…Following prior studies, to derive meaningful and unambiguous clusters, we set thresholds in the network that suppressed coincidental cocitations (Raasch et al, 2013) and excluded loosely connected publications (Small, 1980). In line with common practice (Babl, Schiereck, and Von Flotow, 2014;Meyer, Zaggl, and Carley, 2011), we evaluated the robustness of the network by gradually altering threshold levels for both link strength (L) and component size (C). 8 Our sensitivity analysis (Appendix 1) showed that the network structure is robust and that the selected thresholds of L > .45 and C > 3 allow for a good balance between size and number of individual clusters.…”
Section: Centrality and Cluster Analysismentioning
confidence: 99%
“…Some fields, such as social simulation, have a higher impact on other traditional disciplinary areas outside the social sciences (Squazzoni and Casnisi 2013). Additionally, subareas or social complexity show high degree of thematic and methodological and specialization (Meyer et al 2009(Meyer et al , 2011. This fragmentation eventually hinders the explanatory potential of the advances in these areas of study.…”
Section: Discussionmentioning
confidence: 99%